2011
DOI: 10.1254/jphs.10228sc
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Human Sodium-Phosphate Transporter 4 (NPT4/SLC17A3) Polymorphisms

Abstract: Abstract. We analyzed the functional properties of five nonsynonymous single nucleotide polymorphisms (SNPs) in the sodium-phosphate transporter NPT4 gene (SLC17A3) using the Xenopus oocyte expression system. NPT4 variants carrying SNP V257F, G279R, or P378L exhibited reduced transport of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Since reabsorptive urate by apical proximal tubule transporters may leak back into the tubule lumen via apical urate transporter NPT4, the inhibition of urate transport at NPT4 site by loop diuretics and thiazide diuretics appears consistent with the idea of diuretic-induced hyperuricemia. Our current data and the previous data illustrating 4 as a substrate of NPT4 [14,17] and OAT1/OAT3 [18] support the notion that transepithelial secretory transport of loop and thiazide diuretics in renal proximal tubule is mediated by multispecific OATs, OAT1 and OAT3 at the basolateral side, and also via the apical voltage-driven OAT NPT4. As depicted in Figure 2, these transport processes allow the diuretics to reach their site of action at the thick ascending limb of Henle's loop and distal convoluted tubule.…”
Section: Functional Properties Of Npt4 and Its Localizationsupporting
confidence: 89%
See 2 more Smart Citations
“…Since reabsorptive urate by apical proximal tubule transporters may leak back into the tubule lumen via apical urate transporter NPT4, the inhibition of urate transport at NPT4 site by loop diuretics and thiazide diuretics appears consistent with the idea of diuretic-induced hyperuricemia. Our current data and the previous data illustrating 4 as a substrate of NPT4 [14,17] and OAT1/OAT3 [18] support the notion that transepithelial secretory transport of loop and thiazide diuretics in renal proximal tubule is mediated by multispecific OATs, OAT1 and OAT3 at the basolateral side, and also via the apical voltage-driven OAT NPT4. As depicted in Figure 2, these transport processes allow the diuretics to reach their site of action at the thick ascending limb of Henle's loop and distal convoluted tubule.…”
Section: Functional Properties Of Npt4 and Its Localizationsupporting
confidence: 89%
“…[17] Urate, PAH, estrone sulfate, and bumetanide transport were observed in five NPT4 variants (A100T, G239V, V257F, G279R, P378L). Compared to the wild-type clone, P378L did not show any transport function for all four substrates tested.…”
Section: Single Nucleotide Polymorphisms (Snps) On Slc17a3/npt4mentioning
confidence: 92%
See 1 more Smart Citation
“…NPT1 and NPT4 localize to the apical membrane of RPTECs and are hypothesized to export urate into the tubule lumen as part of the urate secretory pathway. Support for this functional role comes from the identification and analysis of missense mutations involved in hyperuricemia and/or gout that exhibit altered urate transport activities [35,[44][45][46][47]. Moreover, it has been suggested that hyperuricemia induced by diuretics may be due to inhibition of NPT4 [45].…”
Section: Npt1 Npt4 and Npt5mentioning
confidence: 99%
“…cRNA synthesis and uptake measurements were performed as previously described (14). Briefly, the cDNA was linearized with Xba I, and the cDNA insert transcribed in vitro with the T7 mMESSAGE mMACHINE cRNA synthesis kit (Ambion, Austin, TX, USA).…”
mentioning
confidence: 99%